Nostalgia and digital technology: The Gleaners and I (Varda, 2000) and The Triplets of Belleville (Chomet, 2003) as reflective genres. - Fauvel, Maryse (Studies in French Cinema, 2005)
An ironic tension between nostalgia and digital technology permeates Les Glaneurs et la glaneuse and Les Triplettes de Belleville. Both films are political and critical: Varda denounces excess, waste and frivolous behaviour in the contemporary world, while Chomet expresses dissatisfaction with modernity in France. They both recall the past, but acknowledge the impossibility of indulging in nostalgia. Digital technology is foregrounded in both films, and allows Varda and Chomet to offer reflective manifestos, respectively for documentaries and cartoons, in which they highlight a reflection on the world order, on the medium of film, and on specific genres of films.